Estimation of multilayered wall slenderness depending on behaviour of flexible ties/Sluoksniuotųjų sienų liaunio įvertinimas, atsižvelgiant į lanksčių ryšių darbą - Marčiukaitis, Gediminas; Popovas, Vladimiras (Journal of Civil Engineering and Management, 1999)
The problem of slenderness effect of multilayered wall with flexible ties is discussed. Numerical analysis was carried out with the aim to evaluate the influence of rigidity of exterior protective wall layer connected with interior load bearing layer by flexible ties. The buckling effect of layered wall was investigated. The main variables taken into account were thickness of the load bearing and protective layers, the distance between mentioned layers, total amount, diameter and distribution of flexible ties, physical and mechanical properties of wall materials. The results of analysis are discussed and compared with the results of analytical calculation methods. On the basis of numerical simulation data some proposals for buckling coefficient φh calculation were suggested, depending on the structural type of the wall and the total amount of flexible ties distributed between the inner layers. The way of evaluation of the slenderness effect on the general behaviour of multilayered wall is provided additionaly to the requirements of the codes of practice.Article in Lithuanian.First Published Online: 26 Jul 2012